Project management: Shaping dimensions and criteria to achieve success - Imperadeiro, Carlos Manuel Pimenta (2022)
In the last years, economic and social instability created a dynamic environment that forced the need for organisations, through the use of projects, to adapt and evolve to maintain their competitiveness. In this sense, project success became a vital part of the short- and long-term organisation generation of value and performance improvement. This competitive and demanding business environment questioned the traditional measurement of success (i.e., Cost, Time, Scope, and Quality) to include other success dimensions (e.g., Stakeholder's perception). Nevertheless, there's no agreement between project management professionals and researchers about the proper definition of project success. Through a deductive reasoning and a qualitative research strategy, this study aimed to address project success and propose a framework that modern organisations can use to measure the performance of their projects. This study conducted a literature review that analysed the existing frameworks, complemented by a content analysis of semi-structured interviews of fifteen project and programme managers with at least five years of experience in project management through different industry sectors. The study findings allowed the development of a multidimensional project success framework, more comprehensive and with a common language with other success evaluation methods, with four distinct dimensions: (1) Project Efficiency; (2) Business & Strategy Success; (3) Sustainability; and (4) Stakeholder Satisfaction; which can in the future be used by different project researchers to further development of new studies in the project management field and by professionals.